Association of brain-derived neurotrophic factors and tau protein blood levels with delirium patients in intensive care unit - Muslim, Halimatun Sa’adiah (2014)

(untitled)
Background: Delirium, an acute and fluctuating disturbance of consciousness and cognition, frequently occurs in critically ill patients, occurring up to 80% of the critically ill. It is hence associated with several disease severity and infection. As critically ill patients are subjected to numerous risk factors for delirium such as sedative, analgesic agents and pre-existing systemic illness, some of these may be modified to reduce the risk factors for delirium. The aim of the study was to determine the association between serum concentration of brain derived neurotrophic factor (BDNF) and Tau protein levels with delirium in mechanically ventilated ICU patients. Methodology: This was a prospective cross-sectional study from June 2013 until November 2013 done in ICU HUSM. 45 ICU patients with or without delirium were included. Within 12 hours of ICU admission, blood was obtained for baseline biomarker analysis and subsequently 48 hours later, another blood sample was obtained. Delirium was diagnosed by using the Confusion-Assessment Method in ICU (CAM-ICU). ELISA assay for the plasma Tau protein and BDNF were performed to obtain the blood level for these biomarkers. To determine the associations between the blood levels of biomarkers which are Brain-derived Neurotrophic Factors and Tau protein withdelirious patients who are mechanically ventilated in ICU (HUSM), non-parametric analysis were performed. Results: 45 patients were included into this study but 5 were dropped out due to inability to perform CAM-ICU as a result of deep sedation with RASS score ranging from -4 to -5. Until the end of their stay, all drop outs died in ICU. Demographically, patients from the age 18 to 65 years old were included. We found that the median BDNF levels were significantly lower in the delirium patients when compared to the non-delirium patients within the first day of admission, (71.22ng/mL, IqR 33.78 vs 103.76ng/mL IqR 41.91) with p-value of 0.001. There was no significant difference in the median BDNF levels after 48 hours (day 3) from ICU admission between the delirious and non-delirious group, (8.69ng/mL, IqR 10.70 vs 12.16, IqR 10.79), respectively, with a p-value of 0.573.However, for the median of Tau protein on day 1 and day 3, the levels were not statistically significant for either the delirious and the non-delirious group, with day 1 ICU admission having Tau protein levels of 0.18ng/mL, IqR 0.12 vs 0.16ng/mL, IqR 0.10, and with day 3 ICU admission having delirum Tau protein levels of 84.66ng/mL, IqR 122.23 vs non-delirium Tau protein levels 55.48 ng/mL, IqR 30.95, with p-value > 0.005. Median age of patients in ICU was 45 years old accounting 7.5% of all patients. Subsequent division of age range into three groups were done, with younger age from 18 to 35 years old, median age from 36 to 55 years old and older age from 56 to 65 years old. Out of 40 patients, 30%(n=12) were at the younger age group, 32.5% (n=13) were at median age group and 37.5% (n=15) were at the older age group. Among them, it was found that 57.5% (n=23) were delirious and 42.5% (n=17) were non-delirious. 34.78% (n=8) from the delirious group were at younger age, 26.1% (n=6) were at median age and 39.1% (n=9) were at older age. Further results show that among 17 non-delirious patients, 23.5% (n=4) were at younger age, 41.8% (n=7) were at median age and 35.3% (n=6) were at older age. The results show that there were significant differences in the median length of stay between delirium and non-delirium groups, 11(7) and 5(6) respectively, with p-value of 0.003.The length of delirium patients requiring mechanical ventilator (in days) were significantly longer compared to the non-delirium patients, 9(7) and 3(5) respectively, with a p-value of 0.002. In total, it was found that there were more ventilated patients in ICU having delirium at 57.5% (n=23) compared to 42.5% (n=17) for non-delirium patients. Conclusion: This study demonstrates that there was an association between ICU admission levels of BDNF and the occurrence of delirium in ICU patients, in the pathophysiology of ICU delirium, suggesting a role for neuronal death occurring in the pre-ICU delirium setting or soon after admission of within 12 hours, and not during the ICU stay. However, Tau protein levels do not correlate with the occurrence of delirium in ICU.